The Implementation of VCT (Value Clarification Technique) Model in Improving Students’ Responsibility Character on Environment in Indonesia - Dahliar, Dahliar (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research was to develop students’ responsibility character through the implementation of VCT learning and study its effect on students’concern towards enviromental hygiene in state senior high school of Solek Regency. This research employed mixed method research. The data was collected through observation, interview and documentation. To analyze the data, the researcher used simple percentage analysis followed by data reduction, interpretation and conclusion. The result of the study showed that the implementation of learning by using VCT learning model in developing the character of responsibility has been going well. In State Senior High School 1 of Pantai Cermin, students’ responsibility character was going into “start to develop” criteria while in State Senior High School 1 of Lembah Gumanti it was categorized as “Culturized”. The development of resposibility character in both schools was affected by schools’ condition and location.